1983
DOI: 10.1161/01.cir.67.5.1084
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nifedipine on arterial pressure and reflex cardiac control.

Abstract: Nine patients with untreated essential hypertension (mean casual blood pressure 173/109 +/- 14/7 mm Hg) (+/- SD) were studied in the control state and after 16 weeks of treatment with nifedipine, 10 mg orally every 8 hours. Direct arterial blood pressure monitored continuously over 24 hours showed that nifedipine significantly reduced systolic and diastolic blood pressure throughout the day and the night. The variability of blood pressure was not altered by nifedipine therapy. There was no significant change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
3
1

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 16 publications
5
31
3
1
Order By: Relevance
“…We have re-analysed previously published data from our department [1][2][3] on patients given calcium antagonists both acutely and chronically, to determine the influence of dihydropyridine therapy on continuous, spontaneous 24-h baroreflex sensitivity (BRS). Despite having been used routinely in the treatment of hypertension and ischaemic heart disease for 20 years, the safety of calcium antagonists has recently been called into question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have re-analysed previously published data from our department [1][2][3] on patients given calcium antagonists both acutely and chronically, to determine the influence of dihydropyridine therapy on continuous, spontaneous 24-h baroreflex sensitivity (BRS). Despite having been used routinely in the treatment of hypertension and ischaemic heart disease for 20 years, the safety of calcium antagonists has recently been called into question.…”
Section: Introductionmentioning
confidence: 99%
“…8 BRS is impaired in hypertension, but the influence of chronic dihydropyridine therapy on BRS is unclear and the results of previous studies on the effects of calcium antagonists have been inconsistent. [1][2][3]9 Patients and methods Twenty-three patients were included in this reanalysis. Ten were studied after an acute dose of a dihydropyridine calcium antagonist and 21 after chronic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…45 Although it is unlikely that left ventricular mass would be altered to any great extent by 6 weeks of antihypertensive treatment, previous studies in younger subjects with moderate combined hypertension have found left ventricular mass to be significantly reduced after only 16 weeks of nifedipine therapy, so some alteration cannot be entirely discounted. 13 The tilt test examines the integrated response of the cardiovascular system to orthostatic stress and does not discriminate between arterial high-pressure baroreflex responses and those evoked by the cardiopulmonary low-pressure receptors that are stimulated by pooling of blood in the lower limbs. Although the two responses can be separated to an extent by use of low and high-level lower body negative pressure, 46 passive tilt has the advantage of simulating the stresses to which the cardiovascular system is subjected during normal activities and when the drug is used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several studies have addressed the issue of the modification of arterial baroreceptor-cardiac reflex sensitivity (BRS) with antihypertensive treatment in young and elderly subjects, predominantly with either angiotensin-converting enzyme inhibitors [9][10][11][12] or with calcium channel blocking drugs. [12][13][14][15][16][17] The basis for the observed increases in BRS with treatment, although not seen in every study, 17 is thought to be an increase in large artery compliance permitting resetting of baroreflexes. On this basis it could be proposed that elderly subjects with isolated systolic hypertension (ISH), who represent over half of all elderly hypertensives 18 and who have demonstrable reductions in large artery compliance when compared to their peers with combined hypertension [19][20][21] (usually attributed to more advanced arteriosclerosis), may not respond with the same alterations in BRS with treatment as have been described in younger subjects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation